Eklektisme Nilai-nilai dalam Keluarga sebagai Fondasi Pengembangan Kurikulum Pendidikan Bahasa Arab - Hanafi Putra, Wahyu; Mahmudah, Mahmudah; Burdah, Ibnu; Nurbayan, Yayan (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2023)
This research analyzes family values ​​as the foundation for developing an Arabic language education curriculum. This research is qualitative with a library research model. The research data is in the form of family values ​​obtained through several sources: Al-Qur'an, books, and e-journals. The collection technique is carried out with documentation. The author documents family values ​​obtained from various sources and then presents them in tabular form for analysis. The data analysis uses content analysis. The research results show that five values ​​in the family have an eclectic nature for developing the Arabic language education curriculum: communicative, cooperative, creative, responsible, and democratic. The five values ​​in the family have a close intersection, connection, and sustainability for the development of the Arabic language education curriculum in schools and higher education. Family values ​​can be connected to individuals, technology, and information resources in learning. Not all values ​​in the family can be represented in the Arabic language education methodology. Only interactive values ​​can be projected for developing the Arabic language education curriculum.